Pharmacy Students’ Knowledge Assessment of Naegleria fowleri Infection - Sadia Shakeel; Wajiha Iffat; Madeeha Khan (Scientifica)
A cross-sectional study was conducted from April to August 2015 to assess the knowledge of pharmacy students towards Naegleria fowleri infection. A questionnaire was distributed to senior pharmacy students in different private and public sector universities of Karachi. Descriptive statistics were used to demonstrate students’ demographic information and their responses to the questionnaire. Pearson chi-square test was adopted to assess the relationship between independent variables and responses of students. The study revealed that pharmacy students were having adequate awareness of Naegleria fowleri infection and considered it as a serious health issue that necessitates instantaneous steps by the government to prevent the general public from the fatal neurological infection. The students recommended that appropriate methods should be projected in the community from time to time that increases public awareness about the associated risk factors.